Penguatan Keuangan Sederhana dan Kontrol Kualitas Pada UMKM Makanan dan Minuman - Kautsar, Achmad; Fazlurrahman, Hujjatullah; Amelia, Ratih; Sari Dewi , Renny; Septa Wihara, Dhiyan; Fitro, Achmad (Abimanyu: Journal of Community Engagement, 2025)
Based on the results of the interviews, it is still found that the quality standards for the taste of the chips produced by the Ketintang Village MSMEs still change frequently, so it is necessary to organize quality control as well as financial records so that the financial management of MSMEs in Ketintang Village is even better. The solution offered is to provide training on Quality Control and making simple financial reports to improve the performance of MSMEs in Ketintang Village Surabaya. The approach method offered to solve partner problems that have been mutually agreed upon and stages is the training and mentoring method. these results show that the effectiveness of community service activities is almost 80% achieved. Training on Standard Operating Procedures (SOPs) and simple finance provides great benefits for MSMEs in building a more structured and efficient business foundation. From this training, participants gained an understanding of the importance of SOPs as work guidelines to improve operational consistency and quality. In addition, the simple finance training provided insights for businesses on the importance of recording transactions, preparing financial statements, and good cash flow management. By mastering these materials, MSMEs can increase productivity and competitiveness in the market.